Understanding non-English Major’s Students’ Motivation in Learning English via Photovoice: Insights from Tertiary EFL Students - Achmad Kholili; Aziza Restu Febrianto (Universitas Islam Negeri (UIN) Mataram, 2023)
Despite various studies on the motivation in the ELT context, there is a lack of study that centers on the learners’ motivation of non-English majors through photovoice research. The current study attempts to fill this gap. This study was conducted in a private university in Indonesia, involving five non-English major students. A photovoice study was utilized so as to capture and understand their learning motivation. It was found that the photographs the students took illustrated that the students have now been learning English in much more critical ways. Various reasons for their learning English include the ideas that English is a beautiful and a useful language. They also perceived that learning English can help us get a better job; traveling is much easier with a good knowledge of English; and having knowledge of English can help you study abroad. They perceived that they should study English harder to achieve such goals. The findings also show that they belong to non-English majors. Suggestions for future studies are also offered in this paper.